2019
DOI: 10.1186/s40854-019-0122-8
|View full text |Cite
|
Sign up to set email alerts
|

Remittances, financial development and economic growth in sub-Saharan African countries: evidence from a PMG-ARDL approach

Abstract: The study investigated the relationship among remittances, financial development and economic growth in a panel of 20 sub-Saharan African countries over the period of 2000 and 2015. The study used both Pooled Mean Group and Mean Group/ARDL estimations with panel unit root and cointegration tests. After establishing cointegration, remittances and financial development were found to have positive effects on economic growth both in the short and the long run. The interactive term showed that financial development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 50 publications
8
89
1
Order By: Relevance
“…This study employs a pooled mean group or panel ARDL approach because it is appropriate for the studies with small sample size. This study includes 13 countries and 16 years, which is a relatively small sample compared to many studies using panel data (Olayungbo and Quadri, 2019). Arellano and Bond (1991) explained that pooled mean group ARDL and Generalized Method of Moments (GMM) are applicable when the number of periods exceeds the number of cross-sections, i.e.…”
Section: Sample Variable Description and Empirical Modelsmentioning
confidence: 99%
“…This study employs a pooled mean group or panel ARDL approach because it is appropriate for the studies with small sample size. This study includes 13 countries and 16 years, which is a relatively small sample compared to many studies using panel data (Olayungbo and Quadri, 2019). Arellano and Bond (1991) explained that pooled mean group ARDL and Generalized Method of Moments (GMM) are applicable when the number of periods exceeds the number of cross-sections, i.e.…”
Section: Sample Variable Description and Empirical Modelsmentioning
confidence: 99%
“…Currently, numerous studies have found that remittance inflows are another potential source that increases environmental degradation in various economies of the world. The remittance inflows have a vital source of foreign capital which significant positive influence on numerous economies outcomes for example financial development (Olayungbo and Quadri 2019), foreign direct investment (Basnet and Upadhyaya 2014), technological innovation (Tshikala et al 2019), and economic growth (Chowdhury 2016), which are measured as an important indicator for environmental sustainability. The BRICS countries have received a remittance of approximately 1.10$ trillion in 2017; these economies have top remittance receiver's economies among developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Following the studies of (Kumar, 2013;Chowdhury, 2016;Kadozi, 2019;Olayungbo, 2019), we introduce other control variables which have been identified to affect economic growth. Following these studies, we re-specify equation 3…”
Section: Data and Methodology 31 Theoretical Framework And Model Spementioning
confidence: 99%